Bland "rationella asketer" och "ädla vildar" : Etniska relationer inom svensk längdskidsport från sekelskifte till mellankrigstid - Lidström, Isak (Malmö högskola, Institutionen Idrottsvetenskap (IDV), 2017)
Historiskt har längdskidåkningen haft en framträdande plats i den svenskaidrottsnationalismen. Manliga skidåkare har i detta sammanhang fått förkroppsligaett folkhjälteideal där tysthet, strävsamhet, jantelag och skogsarbete varitcentrala beståndsdelar. Etniska relationer inom denna vinteridrott har emellertidhamnat i skymundan, inte minst vid beaktande av skidåkningens betydelse somsamisk identitetsmarkör. Denna uppsats tar därför avstamp i idrottens kontrasteringmellan ”svenskhet” och ”samiskhet” som, visar det sig, var särskilt påtaglig iden moderna skidsportens ungdom. Cross-country skiing in Sweden has long been a sport with connotationsof nationalism. When skiing became a popular sport in the 1920s, an imageemerged of the elite male cross-country skier as a ”folk hero” embodyingcertain characteristics: he was a silent, willful and hard-working lumberjack.The present study contributes to the discussion of identity formation withinSwedish cross-country skiing by adding an ethnic perspective. Although skiinghad an important function in early twentieth-century national identityformation, skiing was also strongly associated with the Sami people, theindigenous population of the Nordic countries who resides in a region thatstretches across the national borders of Sweden, Norway, Finland and Russia.The study analyzes and sheds light on the contrast between ”Swedishness”and ”Saminess” in descriptions of individual elite cross-country skiers inpress material and skiing literature of the early twentieth century.Two ideal types of cross-country skiers, both with connotations of nationalismand ethnicity, emerge from the sources. First, the ”rational ascetic,”representing the characteristics of the ”folk hero.” His industriousness,silence, restraint and unpretentiousness embody a protestant ethic, whichcombines the pursuit of success with an asceticism that prevents the skierfrom being satisfied with his achievements. Athletic skills were therebyexplained as the result of intentions put into practice through rational ...